Wind-Photovoltaic Combined Generation with Grid Connection Using Back-to-Back Voltage Source Converters (International Journal of Innovative Research in Computer Science & Technology, 2022)
Here, we introduce a brand - new  topology, but easy and efficient, for a grid-linked  windphotovoltaic (PV) cogeneration system. A permanent  magnet synchronous generator-primarily based totally full  - scale wind turbine is interfaced to the utility-grid through  back-to-back (Bt-B) voltage-supply converters (VSCs). A  PV sun generator is at once linked to the dc-hyperlink  capacitor of the B-t-B VSCs. No dc/dc conversion stages  are required, and subsequently the system performance is  maximized. The proposed topology capabilities an  unbiased most strength factor monitoring for each the wind  and the PV turbines to maximise the extraction of the  renewable energy. The certain small signal fashions for the  system additives are evolved to look at the general  stability. The effect of the utility-grid faults at the overall  performance of the proposed system is likewise evaluated.  Nonlinear time-domain simulation consequences below  different running situations are supplied to validate the  effectiveness of the proposed topology.
Keywords: PV; Voltage; Turbines; Dc Voltage